Faktor-Faktor Yang Memengaruhi Perilaku Perawat Dalam Pemilahan Limbah Medis Di RS Al Islam Bandung: Factors influencing Nurses Behavior in Sorting Medical Waste at Al Islam Hospital - Asriningrum, Surdiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2018)
The separation of medical waste in Al Islam Hospital Bandung can not befully implemented, it is based on the result of compliance value in wastesegregation in 2016 which done by Household Sector and PSPPRS(Maintenance of Facilities and Infrastructure and Hospital Equipment)obtained 88,37%. This study aims to know, describe and analyze theinfluence of intention, social support, health information or healthfacilities, personal autonomy and the situation to act simultaneously onthe behavior of nurses. The population of this research is 465 nursewhich 40 sample taken using proportional random sampling technique.Data collecting instrumentusing quetionwith likert scale from varioustheory and form it into operation variable, which validity and reliabletest taken to define the original of instrument form. The result statistikanalysis showed that the correlation betwen intention (X1) = -11%,social support (X2) = 0,31%, health information or health facility (X3) =1,1%, personal autonomy (X4) = -0,01% and situation to act (X5) =0,003%, that variable has a positif relation in influencing behaviorchange of nurse.